The Influence of Visual Learning Style and Self-Efficacy Towards Students' Reading Comprehension - Virdaus, Varia Virdania; Rifa’i, Saiful (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
In the context of senior high school education, this study examines the relative contributions of visual learning style and self-efficacy on students' reading comprehension. 120 eleventh-grade students were chosen for the study using stratified random sampling, which was framed inside a quantitative correlational research design. A standardized reading comprehension exam, a self-efficacy scale, and a validated visual learning style questionnaire were among the tools used to collect the data.Self-efficacy emerged as the stronger predictor, however both visual learning style and self-efficacy had a statistically significant impact on reading comprehension, according to multiple regression analysis. These results highlight how crucial it is to support kids' self-belief and cater to their unique learning styles in order to improve reading performance. With a focus on the incorporation of visually enhanced instructional tactics and self-efficacy-enhancing interventions into English language teaching practices, the study provides pedagogical implications for educators and curriculum developers.